A Multifunctional Flexible Ferroelectric Transistor Sensor for Electronic Skin. Issue 24 (12th November 2021) - Liu, Weilin; Lin, Dong; Zeng, Wanyu; Wang, Qinhao; Yang, Jiang; Peng, Zengchong; Zhang, Qun; Zhu, Guodong
Abstract: Electronic skin (E‐skin) is a device that mimics the functions of human skin and is attracting more and more attention as a novel platform for human–machine interaction, health diagnostics, therapeutics, robotics, prosthesis, and monitoring. Here, a flexible ferroelectric field‐effect transistor (FeFET) is developed as a multifunctional sensor prototype for electronic skin. Ferroelectric poly(vinylidene fluoride trifluoroethylene) and amorphous tungsten‐doped indium oxide are utilized to construct the FeFET. The device possesses three‐in‐one sensing performance. It can monitor external stress with a linear sensitivity of 4.6 nA kPa −1 in broad pressure range between 50 Pa and 150 kPa and detect temperature change between 0 and 70 °C. Electrostatic interaction further endows the device with proximity sensing function to perceive the approach of a charged object. The device is further developed for detection of a human's physiological signals, such as pulsation and respiration, and finger's action. It shows good bending endurance which maintains its transfer characteristic after 1000 cycles of bending operation. Moreover, the device's responses to both temperature change and charged objects are investigated when it is under bending condition with radius of curvature down to 1.09 mm. This multifunctional sensor prototype is expected to contribute to the next‐generation E‐skin. Abstract : A flexible ferroelectric field‐effect transistor is developed as a multifunctional sensor prototype. It possesses three‐in‐one sensing performance. It can monitor external stress in a broad pressure range between 50 Pa and 150 kPa and detect temperature change between 0 and 70 °C. Electrostatic interaction further endows the device with proximity sensing function to perceive the approach of a charged object.